The Dakwah Problems of the Muhammadiyah Organization in Cimanggis District, Depok City - Heri Solehudin (Perhimpunan Intelektual Muslim Indonesia, 2023)
Since its birth, Muhammadiyah has determined its missionary line that is straight in line with the social problems of the Indonesian nation, so it is only natural that Muhammadiyah in its da'wah activities is characterized by a number of its Charities (Muhammadiyah Charities), especially in the fields of education and health. Along with the times, social, economic and educational problems in society are increasingly complex, this is where Muhammadiyah is required to play an active role in providing solutions to a number of these social problems. On the other hand, the limitations of both Muhammadiyah human resources and natural resources which are actually very potential in the Cimanggis District, Depok City are also still not fully explored. thus hampering Muhammadiyah missionary activities in Cimanggis District, Depok City. This research is a type of descriptive research with a qualitative approach. While the data collected is based on direct observation, interviews and document studies. The results of the study indicate that the problems faced by Muhammadiyah in Cimanggis District, Depok City in realizing its social da'wah, are because Muhammadiyah's potentials have not been fully explored, both in terms of human resources and natural resources.